ANALISA PENGARUH PROMOTION, PRICE, BRAND IMAGE, E-WOM, PRODUCT QUALITY TERHADAP PURCHASE DECISION PADA KONSUMEN CHATIME KOTA BATAM - Melissa Lestari (Politeknik Bisnis Indonesia, 2023)
The purpose of this study is to analyze the effect of promotion, price, brand image, e-wom, product quality on purchase decisions for Chatime consumers, especially in Batam City. The data analysis method used in this research is descriptive analysis method. Data collection used a survey technique by distributing questionnaires online via Google Forms to the people of Batam City with a sample size of 303 respondents. The tool used in this descriptive analysis study was linear regression using IBM SPSS Statistics Version 26 software. The results showed a significant positive effect by the promotion, brand image, product quality, and price variables on the purchased decision, while the E-WOM variable was found to have a positive effect but not significant to the purchased decision.